The legal concept of e-government - A comparative study between the Sudanese and Iraqi legislations – - Youssef, Yassen Omar; Mahmood, Abdulqader Shakir (Journal of Economic, Administrative and Legal Sciences, 2021)
E-government occupies great importance at the present time as it is considered the effective means in pushing the wheel of development and progress forward, and thus it contributes to the development of countries and the well-being of peoples, citizens, residents and visitors, which represented an incentive for countries to compete and compete among themselves to implement e-government by providing (the legal framework) for what It has a role in eliminating administrative corruption and getting rid of red tape, and the success of this approach by states depends on the extent to which the legislator understands its term and clarifies its concept in a clear and flexible manner that accommodates its application. This study aims to clarify the concept of e-government in Iraqi legislation and comparative laws to find out the divergent trends that I follow. All of them to clarify it, and to clarify the impact of that on the performance of government agencies, in order to ultimately reach a specific concept for it, the two researchers adhered to the descriptive comparative approach when reviewing the concept of e-government, and the position of the legal systems of comparative countries from them. 2005 and the second is a legal basis organized by many legislations, and that e-government in its narrow sense is nothing more than just using the means of modern technology by the public administration to carry out its functions and follow the public need, and therefore the researchers recommend that the issue of e-government be given more attention because of its impact on all aspects Life in any place of the world, preparing all the requirements for the application of e-government and the need to expedite the provision of the necessary legal environment for the implementation of e-government quickly because of its positive role in eliminating administrative and financial corruption and getting rid of annoying red tape and bureaucracy.